IMPLEMENTASI PERATURAN DAERAH KABUPATEN BOGOR NOMOR 11 TAHUN 2012 DALAM PENATAAN MINIMARKET - Wira Lesmana; Rita Rahmawati; M.YGG seran (LPPM Universitas Djuanda Bogor, 2017)
Along with population growth, minimarket business are growing and there are still violations of the Local Regulation No. 11 Year of 2012 about the arrangement of minimarket in Bogor. The purpose of this study is to determine the implementation of the Bogor Regency Regulation No. 11 Year of 2012 about the arrangement of Minimarket, to determine the factors inhibiting the implementation and to analyze the effort in overcoming these obstacles. The theory used in this research is by using a policy implementation model from Merile S. Grindle which stating that the success of a policy will be influenced by two major variables, namely the content of the policy and the policy environment.Researchers used descriptive analysis method with a quantitative approach. Data analysis technique used is by using the calculation of Weight Mean Score (WMS).The results of the implementation of the Bogor Regency Regulation No. 11Year of 2012 in arranging the minimarket obtained an average score of 3.24 which according to the interpretation in moderate category. These results demonstrate that the implementation of the regional regulation has not been fully implemented. There are still many problems in the implementation of the regional regulation such as the incompatibility of District Regulation Bogor No. 11 Year of 2012 in chapter 7 with the Trade Minister Regulation No. 70 Year of 2013 Article 5 in terms of providing an analysis of social and economic conditions of society. There are 320 minimarkets that have not been authorized , about 20% minimarket violating the article 9 regarding with the operational time and there are seven districts that exceed the quota establishment of minimarket. This happens because of decision maker’s less sinchronized among several competent authorities, the human factor is still lacking, and the factors comprehension level of compliance and implementing policies is still weak. Efforts being made to overcome the problem are to do policing minimarket, a moratorium on the establishment of minimarket and reconciled with the policy content of Article 7 Trade Minister Regulation No. 70 Year of 2013. Keywords: Policy Implementation, Regional Regulations, Structuring Minimarket.